The reductive tricarboxylic acid cycle of carbon dioxide assimilation: initial studies and purification of ATP-citrate lyase from the green sulfur bacterium Chlorobium tepidum. - Wahlund, T M (1997)
Carbon dioxide is fixed largely by the reductive tricarboxylic acid (RTCA) cycle in green sulfur bacteria. One of the key enzymes, ATP-citrate lyase, was purified to apparent homogeneity from the moderately thermophilic green sulfur bacterium Chlorobium tepidum. The molecular weight of the native enzyme was about 550,000, and the preponderance of evidence indicated that the protein is composed of identical subunits (Mr of approximately 135,000) which degraded to two major proteins with Mrs of approximately 65,000 and approximately 42,000. Western immunoblots and in vitro phosphorylation experiments indicated that these two species could have been the result of proteolysis by an endogenous protease, similar to what has been observed with mammalian, yeast, and mold ATP-citrate lyase. In addition to apparent structural similarities, the catalytic properties of C. tepidum ATP-citrate lyase showed marked similarities to the eukaryotic enzyme, with significant differences from other prokaryotic ATP-citrate lyases, including the enzyme from the closely related organism Chlorobium limicola. Phosphorylation of C. tepidum ATP-citrate lyase occurred, presumably on a histidine residue at the active site, similar to the case for the mammalian enzyme. In contrast to the situation observed for other prokaryotic ATP-citrate lyase enzymes, the C. tepidum enzyme was not able to replace ATP and GTP for activity or use Cu2+ to replace Mg2+ for enzyme activity. Given the apparent structural and catalytic similarities of the enzyme from C. tepidum and its eukaryotic counterpart, the C. tepidum system should serve as an excellent model for studies of the enzymology and regulation of this protein.